Field-Based Insights into E-Learning, PBL, and Soft Skills Participation in TVET - Wagino; Arif, Ahmad; Martias; Koto, Rahmat Desman; Samala, Agariadne Dwinggo; Criollo-C, Santiago (E3S web of conferences, 2025)
Advancements in technology within education have resulted in an expanded incorporation of digital tools and interactive learning methodologies. Within the realm of Technical and Vocational Education and Training (TVET), there is a growing emphasis on the cultivation of practical skills and employability in response to industry needs. This paper analyses the contribution of e-learning and Problem-Based Learning (PBL) in fostering the development of soft skills, including communication, teamwork, and problem-solving, among TVET students. E-learning gives flexibility and accessibility for self-directed learning, but PBL delivers practical experience in real-world problem-solving via collaborative teamwork. This research used Structural Equation Modelling (SEM) to examine the correlation between the implementation of e-learning and Problem-Based Learning (PBL) in enhancing students' soft skills. The findings indicate that the use of e-learning and problem-based learning methodologies markedly enhances communication, teamwork, and problem-solving abilities among TVET students. All examined factors demonstrated significance, as shown by P-values less than 0.05. The impact of PBL on enhancing cooperation and problem-solving abilities yielded a Pvalue of 0.03, indicating a significant correlation. Simultaneously, elearning had a substantial impact on communication abilities, shown by a Pvalue of 0.02. The results suggest that the amalgamation of e-learning and project-based learning is crucial for enhancing the soft skills development of TVET students, hence bolstering their preparedness to confront obstacles in the workforce.